The effect on human balance of standing with toe-extension - Ku, P.X.; Abu Osman, Noor Azuan; Yusof, A.; Wan Abas, Wan Abu Bakar (Public Library of Science, 2012)
BACKGROUND: Postural balance is vital for safely carrying out many daily activities, such as locomotion. The purpose of this study was to determine how changes in normal standing (NS) and standing with toe-extension (SWT) impact postural control during quiet standing. Furthermore, the research aimed to examine the extent to which the effect of these factors differed between genders. METHODOLOGY/PRINCIPAL FINDINGS: Thirty healthy young adults (age = 21.2±1.3 y; height = 1.63±0.07 m; mass = 56.0±9.3 kg) with no prior lower limb injuries participated in the study. A postural stability test using the Biodex Balance System was used for both NS and SWT conditions. The three measurements from the BBS were Overall Stability Index (OSI), Medial-Lateral Stability Index (MLSI) and Anterior-Posterior Stability Index (APSI). No significant difference was found between NS and SWT in the OSI, MLSI or APSI (F(2, 28) = 3.357, p = 0.077). The main difference between the stability index scores was significant (F(2, 28) = 275.1, p<0.001). The Bonferroni post-hoc test showed significant differences between the OSI and MLSI (p<0.001); the OSI and APSI (p<0.001); and the MLSI and the APSI (p<0.001). Significant differences were found during NS (p<0.001), for the MLSI when compared with the APSI, but this was not found during the SWT condition. Additionally, no gender effects were proven to exist that altered postural sway during quiet standing. CONCLUSIONS/SIGNIFICANCE: This study reveals significant interaction between the stability indices measured; OSI, APSI and MLSI in both NS and SWT. Standing with toe extended does not have a significant impact on an individual's ability to control their balance during normal quiet standing. However, the findings revealed that the sway tendency in the medial-lateral direction might serve as a factor in an individual's ability to regain balance.